دور الثقافة التنظيمية في تفعيل المشاركة في عملية اتخاذ القرار دراسة ميدانية على العاملين الإداريين في الشركة العامة لمرفأ اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى التعرف على دور الثقافة التنظيمية في تفعيل المشاركة في عملية اتخاذ القرار في الشركة العامة لمرفأ اللاذقية. اعتمد البحث المنهج الوصفي وشمل مجتمع البحث جميع العاملين الإداريين في الشركة العامة لمرفأ اللاذقية, أما عينة البحث فهي عينة ميّسرة من العاملين الإداريين بلغت (200) عامل إداري تمّ توزيع الاستبانة عليهم وأعيد منها (182) استبانة كاملة وجاهزة للتحليل الإحصائي, وبنسبة استجابة بلغت (91%). وباعتماد الأساليب الإحصائية المناسبة كان من أهم النتائج التي تمّ التوصل إليها:1- إنّ الانسجام بين العاملين وثقتهم بمدرائهم وتفانيهم في العمل, بالإضافة إلى حرص المديرين على تفويض المرؤوسين وتطوير قدراتهم ومعنوياتهم وتشجيعهم على العمل الجماعي يسهم في تفعيل عملية اتخاذ القرار في الشركة محل الدراسة.2- إنّ تشجيع المديرين للعاملين على الابتكار وحثهم فعلياً على النمو والابتكار وامتلاكهم رؤية وفهم عميق لخلق فرص عمل جديدة والاستفادة من التحديات لزيادة التعلم والنمو يسهم في تفعيل عملية اتخاذ القرار في الشركة محل الدراسة.3- إنّ وضع المديرين لأهداف واضحة ومنظمة وإنجازها بكفاءة وسعيهم لتحقيق الاستقرار والأمن الوظيفي يسهم في تفعيل عملية اتخاذ القرار في الشركة محل الدراسة.4- إنّ تأكيد المديرين على العمل بكفاءة في إنجاز المهام, واهتمامهم بتحقيق أداء جيد في العمل, واستغلال الموارد المتاحة والمحافظة على تحقيق موقع متميز في الأداء والاهتمام بالعاملين وزيادة كفاءتهم ومتابعة إنجازاتهم يسهم في تفعيل عملية اتخاذ القرار في الشركة محل الدراسة.The research aims to identify the role of organizational culture in the activation of participation in decision-making in the General Company for the port of Latakia process. Adopted Find descriptive approach and included the research community all the administrative staff at the General Company for the port of Latakia, the research sample are soft sample of administrative staff totaled (200) administrative workers were distributed the questionnaire to them and returned them (182) questionnaire is complete and ready for statistical analysis, and response rate (91%). And the adoption of appropriate statistical methods was the most important results that have been reached:*The harmony between workers and their confidence Bmadraihm and dedication to work, in addition to the keenness of directors authorized subordinates and develop their abilities and their morale and encourage them to contribute to collective action to activate the decision making process in the company under study.*Encouraging managers to employees urging them to innovate and actually growth, innovation and vision possessing a deep understanding of the creation of new jobs and take advantage of the challenges to increase learning and growth contributes to the activation of the company's decision-making process under study.*The status of directors of the objectives are clear, organized and completed efficiently and their quest for stability and job security contributes to the activation of the decision making process in the company under study.*The confirmation of managers to work efficiently in the completion of tasks, and their interest in achieving a good performance at work, and the utilization of available resources and the preservation of achieving a privileged position in performance and attention to workers and increase their efficiency and follow up their achievements contribute to activating the decision-making process in the company under study.